Penggunaan Media Benda Konkret dalam Meningkatkan Pemahaman Belajar Siswa Kelas IV pada Pembelajaran IPA di Sekolah Dasar - Diva, Fadelina Wizola (Asian Journal of Early Childhood and Elementary Education, 2024)
The low understanding of students in understanding the material of changes in the form of objects in fourth-grade students at SDN 55/I Sridadi is the main problem of this research. This study aims to improve the understanding of fourth-grade students using concrete objects in teaching Science (IPA) material on changes in the form of objects at SDN 55/I Sridadi. The subjects of this study are fourth-grade students at SDN 55/I Sridadi. Data collection techniques used are observation, interviews, and tests. This study uses quantitative research with an associative research type. After conducting research and data processing, the findings obtained are: Through evaluation questions at the end of each cycle of learning, it can determine students' learning outcomes. The initial values of pre-action students are still far below the determined KKM, which is 75. In action cycle 1, the average value is 70.53, which is still below the KKM, and action cycle 2 shows an average value of 89.87. Thus, learning using concrete objects can improve students' understanding of learning.